Dramaturgi Identitas Diri Biduan Waria - Nor Solehah; Dimas Asto Aji An’amta (Huma: Jurnal Sosiologi, 2023)
A transvestite who performs dramaturgical performances when interacting with others and manages the impression he hopes to grow on others of him, through a self-performance that experiences the setting in public. This study aims to find out how transvestite biduan dramaturgizes his identity in the perspective of dramaturgy and the identity of Erving Goffman. In this study, researchers used a type of qualitative research with a phenomenological approach. This research was conducted in Kumai District, West Kotawaringin Regency. The study time starts in January-April 2023. Data collection techniques use observation, interviews and documentation. The main informants in this study were 4 waria who worked as midwives. Data analysis techniques are data reduction, data display and data verification. The results showed that transvestites used masks to cover their faces. Or in other words, some transvestites play different roles between their backstage and frontstage due to their identity as transvestites. The front stage of waria singers almost all plays the front stage well, which is done like dressing men in front of the family and praying in the men's row. The stage behind the transvestite singer truly expresses herself as a woman with all the personality and changes in appearance, including her distinctive style of dress and way of speaking. So then waria expressed this sexual orientation selection through the way they dressed, where waria subjects in this study stated that their sexual orientation was directed towards men.